Komunikasi Orang Tua Asuh dan Teman Sebaya pada Remaja Yatim Piatu terhadap Perilaku Seksual di Panti Asuhan - Nur Gilang Fitriana; Roro Kushartanti (Universitas Ivet, 2022)
Adolescence is a period of individual life where there is psychological exploration to determine self-identity. This study aims to identify the relationship between parents and friends' communication on sexual behavior. This research is a quantitative study with a cross sectional design. A sample of 80 people. The research was conducted from September 20 to October 28, 2022. Data collection was carried out using a questionnaire. The results of the statistical analysis test on the relationship between foster parent communication and risky sexual behavior were based on the Spearman rho test with a significance value of p=0.001 and r=-0.365. The p value is less than 0.05 and the majority of respondents communicate with peers who are and engage in moderate-risk sexual behavior as many as 25 children (31.2%). The test results of statistical analysis of the relationship between peer communication and risky sexual behavior based on the Spearman rho test with a significance value of p = 0.002 and r = -0.338. The p value is less than 0.05.